Axon mimicking hydrophilic hollow polycaprolactone microfibres for diffusion magnetic resonance imaging. (5th January 2018) - Zhou, Feng-Lei; Li, Zhanxiong; Gough, Julie E.; Hubbard Cristinacce, Penny L.; Parker, Geoff J.M.
Abstract: Highly hydrophilic hollow polycaprolactone (PCL) microfibres were developed as building elements to create tissue-mimicking test objects (phantoms) for validation of diffusion magnetic resonance imaging (MRI). These microfibres were fabricated by the co-electrospinning of PCL-polysiloxane-based surfactant (PSi) mixture as shell and polyethylene oxide as core. The addition of PSi had a significant effect on the size of resultant electrospun fibres and the formation of hollow microfibres. The presence of PSi in both co-electrospun PCL microfibre surface and cross-section, revealed by X-ray energy dispersive spectroscopy (EDX), enabled water to wet these fibres completely (i.e., zero contact angle) and remained active for up to 12 months after immersing in water. PCL and PCL-PSi fibres with uniaxial orientation were constructed into water-filled phantoms. MR measurement revealed that water molecules diffuse anisotropically in the PCL-PSi phantom. Co-electrospun hollow PCL-PSi microfibres have desirable hydrophilic properties for the construction of a new generation of tissue-mimicking dMRI phantoms. Graphical abstract: Highlights: An inclusion of polysiloxane-based surfactant (PSi) into PCL solution improved the hydrophilicity of electrospun PCL fibres. Electrospun PCL-PSi fibres remained hydrophilic over a time period of up to 12 months. EDX analysis confirmed Si distribution on fibre surface and cross-section, which is responsible for the wettability of PCL-PSi fibres. Hollow PCL-PSi microfibres were only produced via co-electrospinning of a miscible combination of shell and core solutions. Phantoms were constructed from hollow PCL and PCL-PSi fibres, and water was detected by dMRI only from the latter.